2018
DOI: 10.1038/s41387-018-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Wdr13 and streptozotocin-induced diabetes

Abstract: Type I diabetes, though contributes to only 5–10% of total diabetes cases, is a rising concern in today’s world. Our previous studies have shown that the absence of WDR13 in mouse results in pancreatic β-cell hyper-proliferation. Also, amelioration of the diabetic phenotype on introgression of Wdr13-null (Wdr13-/0) mutation in genetically diabetic mice (Leprdb/db) [type II diabetes] was observed. It was thus, interesting to see the role of WDR13 in streptozotocin-mediated diabetes in mice, a model for type I d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As a result, 477 up regulated and 383 down regulated genes, at least 4-fold change between T1DM and normal control samples. Wang et al [42], Mishra et al [43], Deaton et al [44] and You et al [45] demonstrated that altered expression of SPHK1, WDR13, GIGYF1 and DNMT3A were found to be substantially related to type 2 diabetes mellitus. Altered expression of SPHK1 [46] was easily found in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 477 up regulated and 383 down regulated genes, at least 4-fold change between T1DM and normal control samples. Wang et al [42], Mishra et al [43], Deaton et al [44] and You et al [45] demonstrated that altered expression of SPHK1, WDR13, GIGYF1 and DNMT3A were found to be substantially related to type 2 diabetes mellitus. Altered expression of SPHK1 [46] was easily found in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was induced by intraperitoneal administration of multiple low doses of streptozotocin (MLD-STZ) to experimental female mice. The STZ was dissolved in freshly prepared 0.1M citrate buffer (pH = 4.5) and was administered (50mg/kg body weight/mice) 10 intraperitoneal for consecutive 5days. .…”
Section: Experimental Designmentioning
confidence: 99%
“…Earlier studies on WDR13 suggest its involvement in cell cycle regulation in different tissues like pancreas (7)(8)(9), liver (10) adipose (11), colon (12) and uterus (13). Wdr13 expression has also been reported in many human cancers like breast cancer, glioma, Ewing's sarcoma, lung cancer, melanoma, testes cancer, ovary teratocarcinoma, and urothelial cancer (Human protein atlas http://www.proteinatlas.org/ENSG00000101940-WDR13/cancer).…”
Section: Introductionmentioning
confidence: 99%